BRAC in PPP pilot intervention: a new initiative of BRAC health programme, quarterly report, March-May 2002 - BRAC (© BRAC, 2016)
1. Introduction 2. Programme strategy 3. Programme implementation 4. Operational activities 5. Participation in PPP study tour 6. Plan for next quarter